1981
DOI: 10.1152/jappl.1981.51.5.1220
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary injury in rats following continuous exposure to 60% O2 for 7 days

Abstract: Morphological, biochemical, and physiological studies were done on rats exposed to 60% O2 for 7 days. This exposure did not induce O2 tolerance but instead caused a significant decrease in survival time of animals subsequently exposed to pure O2. The activity of lung superoxide dismutases and glucose-6-phosphate dehydrogenase were unchanged after exposure to 60% O2. A decrease in lung compliance was suggested by changes in the total lung capacity and in the pressure-volume curves of excised lungs. Ventilation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 17 publications
1
26
0
1
Order By: Relevance
“…In the ference of cytochrome oxidase or peroxidase with the assay. In control group and the NDH group subjected to a 5-h period of lysates of rat erythrocytes, we found the CuZnSOD to be 9.7 ventilation with room air or pure oxygen immediately after birth, times more active at pH 10.2 than at pH 7.8, which is in SOD, catalase, and GPX activity remained at about the initial accordance with earlier reports (15). Because manganese SOD level (Table 3).…”
Section: Original Reports By La~hmann El A/ (1 1) On Artificial Ventsupporting
confidence: 90%
“…In the ference of cytochrome oxidase or peroxidase with the assay. In control group and the NDH group subjected to a 5-h period of lysates of rat erythrocytes, we found the CuZnSOD to be 9.7 ventilation with room air or pure oxygen immediately after birth, times more active at pH 10.2 than at pH 7.8, which is in SOD, catalase, and GPX activity remained at about the initial accordance with earlier reports (15). Because manganese SOD level (Table 3).…”
Section: Original Reports By La~hmann El A/ (1 1) On Artificial Ventsupporting
confidence: 90%
“…704 Bitterman et al General concepts ofpulmonaryfibrosis Independent of cause, the fundamental anatomical feature of pulmonary fibrosis is an increased number of fibroblasts within the alveolar wall. Qualitative studies in humans (30,31), as well as morphometric studies in animals (10,11,32), indicate a several-fold increase in fibroblast number in these disorders. As a result of this expansion of the lung fibroblast population, there tration is increased two-to fivefold (40).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, several studies have shown that bovine (49), murine (50), and hamster (45) (18)(19)(20)(21)(22)(23)(24). Second, rigorous demonstration of increased numbers of alveolar macrophages by morphometry has been performed in several animal models of inflammatory lung disorders (51)(52)(53) and in small numbers of human smokers (54). Finally, quantitation of the numbers of macrophages recovered by bronchoalveolar lavage indicates that individuals with chronic lung inflammation have a substantial increase in the number of macrophages in the alveolar compartment accessible to that procedure (55).…”
Section: Discussionmentioning
confidence: 99%